2020
DOI: 10.1038/s41598-020-62706-4
|View full text |Cite
|
Sign up to set email alerts
|

Effective medium theory to the description of plasmonic resonances: Role of Au and Ti nanoparticles embedded in MoO3 thin films

Abstract: The growing interest in functional transition metal oxides for efficient energy consumption or in the bio-sensing process; indicates that is necessary to develop a new theoretical method that describes experiments. This article presents a new theoretical methodology to characterize molybdenum trioxide (MoO 3) thin films doped with resonant gold-nanoparticles (Au-NPs) and non-resonant titaniumnanoparticles (Ti-NPs). The modulation of surface plasmon resonance (SPR) and the implications in the MoO 3 transmittanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…In all comparative cases, it is observed that in the β -phase of MoO 3 , the extinction coefficient peaks display the highest intensity when compared to the α -phase. This behavior is important to highlight due to the advantages in technological applications where this information could be used to simulate the visible radiation trapping layer by modifying only the molybdenum oxide phase and corroborates what was found previously [ 22 ]. Additionally, by increasing the radius size of the nanoparticle from 5 to 20 nm, the SPR signal shows a redshift in all comparative cases.…”
Section: Absorbance and Extinction Coefficients Of Moo 3 Thin Films Doped By Resonant Npssupporting
confidence: 88%
See 2 more Smart Citations
“…In all comparative cases, it is observed that in the β -phase of MoO 3 , the extinction coefficient peaks display the highest intensity when compared to the α -phase. This behavior is important to highlight due to the advantages in technological applications where this information could be used to simulate the visible radiation trapping layer by modifying only the molybdenum oxide phase and corroborates what was found previously [ 22 ]. Additionally, by increasing the radius size of the nanoparticle from 5 to 20 nm, the SPR signal shows a redshift in all comparative cases.…”
Section: Absorbance and Extinction Coefficients Of Moo 3 Thin Films Doped By Resonant Npssupporting
confidence: 88%
“…This latter configuration has generated significant interest due to the ability to modulate the absorbance in the visible range, a feature of great importance in photocatalytic applications, biological sensing, smart windows, and photovoltaic cells [ 22 ]. This property is attributed to a phenomenon called superficial plasmon resonance (SPR) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several quasianalytical models have been developed for characterizing the nanoaggregate structures, including the effective medium model [ 11 ], cluster-cluster aggregation (CCA) model [ 12 ], and fractal lossy antennas (FLA) model [ 13 ]. The effective medium model simplifies complex nanoclusters into hypothetical ellipsoids.…”
Section: Introductionmentioning
confidence: 99%
“…Напыленные в вакууме ПМП (особенно после их термического отжига) можно представить в виде ансамбля наночастиц, самоорганизованных поверх сплошной металлической поверхности [13]. Ранее было показано [14][15][16][17][18][19][20], что расширенная теория Максвелла-Гарнетта вполне приемлема для соотнесения эффективной диэлектрической функции с подобной морфологией поверхности. Таким образом, анализ возможностей и ограничений разных моделей приводит к выбору расширенной теории Маквелла-Гарнета для моделирования процессов отражения света плазмонными металлическими пленками.…”
Section: Introductionunclassified